2017
DOI: 10.1371/journal.pone.0185326
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial resistance in clinical Escherichia coli isolates from poultry and livestock, China

Abstract: Poultry and livestock are the most important reservoirs for pathogenic Escherichia coli and use of antimicrobials in animal farming is considered the most important factor promoting the emergence, selection and dissemination of antimicrobial-resistant microorganisms. The aim of our study was to investigate antimicrobial resistance in E. coli isolated from food animals in Jiangsu, China. The disc diffusion method was used to determine susceptibility to 18 antimicrobial agents in 862 clinical isolates collected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

20
65
9
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(108 citation statements)
references
References 25 publications
20
65
9
4
Order By: Relevance
“…More recently, a study sampled 862 clinical isolates of E. coli from a variety of animals including chickens, pigs, and cows and found that 94% of strains were resistant to one drug and 83% were resistant to three antimicrobial classes (Yassin et al, 2017).…”
Section: Studies Have Shown That Approximately 54% Of Predominantmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, a study sampled 862 clinical isolates of E. coli from a variety of animals including chickens, pigs, and cows and found that 94% of strains were resistant to one drug and 83% were resistant to three antimicrobial classes (Yassin et al, 2017).…”
Section: Studies Have Shown That Approximately 54% Of Predominantmentioning
confidence: 99%
“…More recently, a study was carried out where 137 E. coli clinical isolates were tested for resistance to 11 commonly used antibiotics and showed 50 of the isolates tested were resistant to 10 of the 11 antibiotics, highlighting the urgent requirement for alternative therapies (Olorunmola, Kolawole, & Lamikanra, ). More recently, a study sampled 862 clinical isolates of E. coli from a variety of animals including chickens, pigs, and cows and found that 94% of strains were resistant to one drug and 83% were resistant to three antimicrobial classes (Yassin et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Increasing antibiotic resistance and the lack of new antibacterial agents have revived 260 interest in old compounds such as nitrofurantoin in clinical [46,47]. Despite the renewed 261 importance of nitrofurantoin and the known role of food animals in resistance 262 dissemination, only a few studies include this antibiotic in antimicrobial resistance 263 screenings [48,49].…”
mentioning
confidence: 99%
“…resistance to nitrofurantoin in extra-intestinal clinical isolates of E. coli from chickens has 267 been reported in China [48]. Due to the possibility that the resistance to nitrofurantoin 268 could increase over time, it is important to include it in antimicrobial resistance 269 surveillance plans in poultry production systems.…”
mentioning
confidence: 99%
“…The variation in resistance reflects the difference in the antimicrobial usage policy of this drug in food-producing animals among the different countries (Kools et al, 2008). China and Brazil use fluoroquinolones for the treatment and prevention of infections in chickens (Gouvêa et al, 2015;Yassin et al, 2017).…”
Section: Quinolonesmentioning
confidence: 99%